Abnormalities of neutrophil function do not cause the migration defect in Crohn's disease. Issue 10 (October 1981) - Moráin, C O; Segal, A A; Walker, D; Levi, A J
Abstract : Skin window tests were performed on 60 patients with Crohn's disease, 20 with ulcerative colitis, 16 with peptic ulceration, and 40 healthy controls. The numbers of neutrophils that migrated into the skin window chambers were significantly lower in patients with Crohn's disease. This abnormality was unrelated to the activity of the disease, site of involvement, or treatment. No significant abnormalities were found in the patients with other diseases of the gastrointestinal tract. The abnormality of neutrophil migration in the Crohn's patients does not seem to be due to a cellular defect, as neutrophils from patients with Crohn's disease migrate and phagocytose normally in vitro. Sera from patients with Crohn's disease did not inhibit cell migration or contain inhibitors of chemotaxis. The addition of serum that had been activated with zymosan to the chamber enhanced the emigration of neutrophils from the skin of patients with Crohn's disease. These results suggest that the depression of neutrophil migration into skin windows that is normally observed in Crohn's disease is due to a deficient local inflammatory response. This defective inflammatory response in Crohn's disease and the consequent delay in the accumulation of neutrophils could explain granuloma formation, the high recurrence rate after surgery, and the clinical course of exacerbations and remissions.